Conflict Management In The Story Of Hadithul Ifki (Quran Study Of Surah Annur Verse 11-20) - Latif, Muhamad Abdul; Ismail, Nawari; Fauzan, Aris (Program Studi Pendidikan Agama Islam Fakultas Ilmu Tarbiyah Dan Keguruan UIN Raden Fatah, 2024)
Humans are social beings who need interaction and communication between them. Social media is the most effective tool, but, unfortunately, there are still many social media that are identified as sites for spreading fake news. The world of education is also not spared from the spread of fake news filled with hostility. The same thing happened at the time of the Prophet Muhammad, which was enshrined in the Qur'an as a defense against the accusation of adultery against Aisha. This research article aims to find out the conflict management that was applied by the Prophet Muhammad when facing slander in the hadithul ifki story as stated in the interpretation of Ath Tabari and the Qur'an and its Tafsir. This type of research uses qualitative research with library research data sources. The method used in this research article is by examining and studying various related literature. The researcher used descriptive and content analysis to analyze the data. The research findings are in the form of conflict management applied by the Prophet Muhammad in the story of hadithul ifki or fake news to Aisyah. The steps for conflict management carried out by the Prophet Muhammad were: first, collecting as much information as possible from the community that triggers the emergence of conflict and a neutral society. Second, to confirm some of the scattered information. Third, affirm the person who is the source of the conflict.